2013
DOI: 10.1186/1471-213x-13-31
|View full text |Cite
|
Sign up to set email alerts
|

The role of Zic transcription factors in regulating hindbrain retinoic acid signaling

Abstract: BackgroundThe reiterated architecture of cranial motor neurons aligns with the segmented structure of the embryonic vertebrate hindbrain. Anterior-posterior identity of cranial motor neurons depends, in part, on retinoic acid signaling levels. The early vertebrate embryo maintains a balance between retinoic acid synthetic and degradative zones on the basis of reciprocal expression domains of the retinoic acid synthesis gene aldhehyde dehydrogenase 1a2 (aldh1a2) posteriorly and the oxidative gene cytochrome p45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Of the known aldh1a genes expressed in early zebrafish development, only aldh1a2 is expressed in pre-hematopoietic posterior mesoderm (Fig 1A–1C; [40–42]). Consequently, to determine if RA regulates zebrafish HSC formation, we generated RA-deficient embryos by injecting embryos with aldh1a2 morpholino (hereafter referred to as aldh1a2 -morphants) [41, 43], or by treating them with Diethylaminobenzaldehyde (DEAB), a competitive inhibitor of aldehyde dehydrogenases including Aldh1a2 [31, 32].…”
Section: Resultsmentioning
confidence: 99%
“…Of the known aldh1a genes expressed in early zebrafish development, only aldh1a2 is expressed in pre-hematopoietic posterior mesoderm (Fig 1A–1C; [40–42]). Consequently, to determine if RA regulates zebrafish HSC formation, we generated RA-deficient embryos by injecting embryos with aldh1a2 morpholino (hereafter referred to as aldh1a2 -morphants) [41, 43], or by treating them with Diethylaminobenzaldehyde (DEAB), a competitive inhibitor of aldehyde dehydrogenases including Aldh1a2 [31, 32].…”
Section: Resultsmentioning
confidence: 99%
“…Zic2a and 2b are expressed in the gastrula mesoderm (Drummond et al, 2013; Grinblat and Sive, 2001; Toyama et al, 2004), including the prechordal plate, which induces formation of the hypothalamus in the ventral diencephalon (Mathieu et al, 2002; Pera and Kessel, 1997; Rubenstein et al, 1998). The hypothalamus subsequently becomes an important source of Shh and is required for regionalization of the anterior diencephalon and optic fissure (Shimamura and Rubenstein, 1997; Zhao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Categories of a cell type that was positive for a given element are color-coded, with a GFP-expressing cell. 22,23 Therefore, the extended version of CNE12030 was shown to drive expression in the habenula, which coincided with the zic3 expression domain. The percentage of GFPexpressing embryos per CNE is indicated beneath each schematic (EE = %).…”
Section: Cne12030 Drives Gfp Expression In the Habenulamentioning
confidence: 89%
“…Moreover, RNA in situ hybridization using an antisense probe against zic3 ( Figure 3N,O) showed that CNE12030 transgene expression coincided with known sites of zic3 expression. 22,23 Therefore, the extended version of CNE12030 was shown to drive expression in the habenula, which coincided with the zic3 expression domain.…”
Section: Cne12030 Drives Gfp Expression In the Habenulamentioning
confidence: 89%